Contrast of Youth Labor Supply and Demand in the Periods before and after the Economic Opening in Colombia (2018)
This paper seeks to stablish the main changes between the periods before and after the economic opening of Colombia, with respect to youth demand and youth supply, through an exploratory-descriptive analysis with a longitudinal cut of three periods oftime. The source of the data begins from the findings of the work of Ocampo (1986) based on the Encuesta Nacional de Hogares and a new elaboration of data analysis of the same survey, in a period after the economic opening. This document also makes a brief bibliographic description where it is shown studies that arise from the concern of analyzing the same macroeconomic variables studied by Ocampo and the present document, and thanks to this a series of hypotheses are elaborated that are contrasted with the results of the survey. Among the main findings we find that after the opening, there is a greater proportion of young people in the employed population, the financial and industrial sectors employ the majority of young people, there are currently more technicians and technologists than university students in the jobs and there is a precarization of income considerably.